(3GdfXGe GdeLRi GdOGFQ Hjf GdjMjhi hGdMeRhi Mhd MH Bd GdHjJ Ydjge GdSdGes - (3GdefUhQ HGddg GdMSf Hf eMeO Hf CMeO Hf jMji Hf jMji Hf GdgGOj Gdj GdMb jMji Hf GdMSjfs
(3ChdgG (B:s
(3YdGe haje jYPGfi Zhi haje jdhefi NH Ndi s
(3BNQgG (B:s
(3JQcJ dge CNGc aCKbhg hQMJ cCf JMJc CMOQi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG TQhM hJUMjMGJs
(3hgh bUjOI ddefUhQ HGddg GdMSf Hf eMeO Hf CMeO Hf jMji Hf jMji Hf GdgGOi Edi GdMb jMji Hf GdMSjf s
(3hQO dYR GdOjf eMeO Hf CMeO Hf YHO Gddg Hf MeRI Ke ELGHI dYeGO GdOjf GdegOi Hf JGL GdOjf Hf CMeO Hf eMeO Hf CMeO Hf jMji s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3Gdabg GdESdGejs